Reproductive Cycle Of The Razor Clam Solen Regularis Dunker, 1862 In The Western Part Of Sarawak, Malaysia, Based On Gonadal Condition Index - Rinyod, A.M.R.; Siti Akmar Khadijah, Ab Rahim (Penerbit UMT, 2011)
Razor clam or ‘ambal’ is a highly-priced bivalve collected as food source from several intertidal areas located in western Sarawak, which currently is an unregulated fishery. This study monitored the reproductive cycle of razor clam, Solen regularis, collected from the intertidal beaches of Asajaya Laut and Buntal using gonadal condition index (GCI). Sampling was performed at a two-weeks interval or monthly for two years from March 2007 to February 2009. A total of 30 specimens were dissected per sampling. The male gonads appeared beige in colour while female gonads were whitish. Throughout the study, the mean GCI ranged from 0.000 (± 0.000) to 0.247 (± 0.077) at Asajaya Laut and 0.000 (± 0.000) to 0.253 (± 0.079) at Buntal. Based on the mean GCI pattern, it is concluded that this razor clams has five stages of reproductive cycle as follows; i) gonadal development, ii) maturation, iii) spawning, iv) spent, and v) resting period. Spawning period for both sites was similar, from end of March-April to September and followed by a short spent stage from end of September-October to November and a resting period from end of October-November to January in the following year. The results obtained in this study could provide important knowledge in determining the spawning season which will benefit razor clam fishery for sustainable management and potential species for aquaculture in future.